Assessing the Impact of Covid19-Pandemic on the Household Income in Kamuganguzi Sub-County Kabale District. - Arinda, Redeemer Present (Kabale University, 2024)
The study focused on the impact of COVID-19 on household income in Kamuganguzi sub-county, Kabale district. The research objectives were to determine the effects of the COVID-19 pandemic on household income in Kamuganguzi sub-county, identify the coping mechanisms households adopted in response to these effects, and assess the extent to which these coping mechanisms succeeded in alleviating the impact of COVID-19 on household income. A descriptive research design was used, incorporating both qualitative and quantitative data. The sample size consisted of 90 respondents from Kamuganguzi sub-county.The study's findings revealed that male respondents comprised 56.7% of the participants, and married respondents accounted for 64%. Additionally, 33.3% of respondents reported that reduced food rations, leading to famine, were a major effect of COVID-19 on families. The study's recommendations included the following: The government should increase spending on immediate health-related expenditures, such as supplies of masks, gloves, other personal protective equipment, ICU beds (Uganda currently has only 55 functional ICU beds, resulting in approximately 1.3 ICU beds per million Ugandans), and ventilators. The government should also ensure that some of the reallocated health sector budget supports non-COVID-19 health concerns, from basic to emergency healthcare. Large-scale testing is necessary to address the pandemic and treat the sick, as without it, the economic and social impact is likely to be prolonged and exacerbate the problem. Innovative approaches, such as using artificial intelligence in high-risk/high-traffic sites to enhance COVID-19 detection efficiency while protecting medical staff and the general public from cross-infections, should be considered. Additionally, the government should establish a physical and automated platform for coordination and resource mobilization to support poor students and the most vulnerable groups affected by COVID-19-related lockdowns.